Optimizing in vitro introduction of wild common hop (Humulus lupulus L.) specimens using plant hormones - Olga V. Bychkova; Olga N. Mironenko; Elena P. Myakisheva; Inga Yu. Ivanova; Dmitry A. Dementiev (Acta Biologica Sibirica)
Hop (Humulus lupulus L.) is a perennial crop propagated vegetatively. There are a number of problems associated with preserving the gene pool, obtaining certified planting material, and replenishing the collection of hop varieties. To solve these problems, it is promising to use biotechnological methods and attract genetic resources from natural flora. The article presents the results of an experimental research on introducing into tissue culture and studying the effect of cytokinin growth regulators on in vitro reproduction of wild hop genotypes from the Altai Krai. A comparison with the in vitro morphogenesis of varieties bred in Russia is provided. Wild hop samples have been shown to be successfully introduced into tissue culture at a level not lower than that of national varieties and are characterized by intensive growth of shoots and root systems in hormone-free Murashige and Skoog (MS) medium. The ANOVA results confirmed that the genetic characteristics of the samples had the greatest impact on the reproduction rate and height of hop plants in vitro culture. The second most important factor was the type of plant growth regulator. The maximum height of the shoots of the ‘Flagman’ variety and the wild sample AK-3 was in the MS nutrient medium containing 5 μM kinetin, and for the ‘Civil'skij’ variety – 1 μM 6-benzylaminopurine. For the AK-1 genotype, the best results were obtained in hormone-free MS medium. The reproduction rate, calculated as the ratio of the the height of shoots, including the lateral ones, to the number of internodes, ranged from 3.9 to 9.1. For wild samples, it was possible to achieve reproduction rates of 8–9 in one passage lasting 8 weeks. The results confirmed the high morphogenetic potential of wild hop samples AK-1 and AK-3 from the south of Western Siberia, as well as the national variety ‘Flagman’ for the use of clonal micropropagation technology to preserve genotypes in the in vitro collection, breeding, and production of planting material.